2016
DOI: 10.15252/embr.201541612
|View full text |Cite
|
Sign up to set email alerts
|

A role for septin 2 in Drp1‐mediated mitochondrial fission

Abstract: Mitochondria are essential eukaryotic organelles often forming intricate networks. The overall network morphology is determined by mitochondrial fusion and fission. Among the multiple mechanisms that appear to regulate mitochondrial fission, the ER and actin have recently been shown to play an important role by mediating mitochondrial constriction and promoting the action of a key fission factor, the dynamin‐like protein Drp1. Here, we report that the cytoskeletal component septin 2 is involved in Drp1‐depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 75 publications
(149 reference statements)
1
74
1
Order By: Relevance
“…As outlined above individual septin family members can thereby exert distinct effects, depending on their subcellular localizations. This is exemplified by SEPT2, which is recruited to the plasma membrane, to endosomal membranes or to the surface of mitochondria, where it controls unique events (the formation of phagocytic carriers, endosomal membrane fusion or organelle fission, respectively) (Huang et al, 2008; Mostowy and Cossart, 2011; Phan et al, 2013; Dolat and Spiliotis, 2016; Pagliuso et al, 2016). Thus, specificity in SEPT2 membrane recruitment and function must be accomplished through additional factors.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above individual septin family members can thereby exert distinct effects, depending on their subcellular localizations. This is exemplified by SEPT2, which is recruited to the plasma membrane, to endosomal membranes or to the surface of mitochondria, where it controls unique events (the formation of phagocytic carriers, endosomal membrane fusion or organelle fission, respectively) (Huang et al, 2008; Mostowy and Cossart, 2011; Phan et al, 2013; Dolat and Spiliotis, 2016; Pagliuso et al, 2016). Thus, specificity in SEPT2 membrane recruitment and function must be accomplished through additional factors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, septin association with sources of membrane in the cytosol remains to be established. New studies have shown that septins interact with mitochondria and enable mitochondrial fission, in a process called mitokinesis (Pagliuso et al, 2016; Sirianni et al, 2016). Strikingly, septin function at the plasma membrane (e.g., phagocytosis, cytokinesis) and in the cytosol (e.g., septin caging, mitokinesis) all involve actin and non-muscle myosin II (Mostowy and Cossart, 2012; Sirianni et al, 2016).…”
Section: Septin Interactions With Intracellular Bacterial Pathogensmentioning
confidence: 99%
“…SEPT2 and 7, by interacting with DRP1 would concentrate it at the sites of mitochondrial constriction and facilitate their fission (Pagliuso et al, 2016; Sirianni et al, 2016). Mitochondria-associated septins also comprise the isoform 2 of SEPT4 (SEPT4_i2) also called ARTS, which upon pro-apoptotic stimuli, is released in the cytosol where it binds to the XIAP proteins to release the inhibition of caspases and thus promote apoptosis (Edison et al, 2012).…”
Section: Localization-dependent Roles Of Septins In Interphase Cellsmentioning
confidence: 99%